Combined linear and non-linear controller design for motor position regulation - Cheng, Guoqing (Electronics letters, 2018)
A composite robust controller is proposed for typical motor servo systems subject to control saturation and unknown disturbance. The controller contains a linear servo control law which achieves a fast response, and a non-linear control part to suppress the overshoot. The unknown disturbance is assumed to have a constant rate of change, and is treated as an extended state of the system. A reduced-order observer is then designed to estimate the unmeasurable state and disturbance for control and compensation. The controller is applied to a permanent magnet synchronous motor for position regulation, and digital simulation and experimental test are conducted to verify the superior performance and robustness of the design.